3D computer model of the Co-Cu-CoS-Cu2S subsystem T-x-y diagram above 800°C - Lutsyk V.I.; Vorob'eva V.P.; Zelenaya A.E.; Lamueva M.V. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The three-dimensional computer model of the Co-Cu-CoS-Cu2S subsystem T-x-y diagram at temperatures above 800°C is represented. It is shown that the liquid immiscibility in the binary subsystem Cu-Cu2S is transformed within the ternary system with Co into the wide two-phase region of two immiscible melts, which interrupts the univariant curve of the Co and Cu2S co-crystallization. The special features of the structure of the solidus surface of cobalt, caused by liquid-phase immiscibility are considered.